2016
DOI: 10.1093/dnares/dsw035
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between genome reduction and bacterial growth

Abstract: Genome reduction by removing dispensable genomic sequences in bacteria is commonly used in both fundamental and applied studies to determine the minimal genetic requirements for a living system or to develop highly efficient bioreactors. Nevertheless, whether and how the accumulative loss of dispensable genomic sequences disturbs bacterial growth remains unclear. To investigate the relationship between genome reduction and growth, a series of Escherichia coli strains carrying genomes reduced in a stepwise mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(144 citation statements)
references
References 48 publications
(51 reference statements)
9
124
2
3
Order By: Relevance
“…A correlation between the growth rate and genome reduction has been previously reported according to the manual calculation [34]. The same conclusion was drawn from the theoretical fitting suggested here, and the modified logistic model was applicable.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A correlation between the growth rate and genome reduction has been previously reported according to the manual calculation [34]. The same conclusion was drawn from the theoretical fitting suggested here, and the modified logistic model was applicable.…”
Section: Resultssupporting
confidence: 87%
“…The raw data sets of these growth curves can be found at Springer Nature Research Data Support and can be accessed online via the following URL: 10.6084/m9.figshare.5918608. The details regarding the determination of the growth data set was previously described [27, 34], and the data sets of growth in M63 and LB media were used in the present study. Evaluation of the models (goodness of fit) was assessed based on the sum of squares, which were calculated according to the following equations.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of colonization, a highly specialized population may lead to a higher rate of survival over the dispersal and also a higher rate of success in the introduction into new areas. Recent experimental observations have revealed a link between genome reduction and a growth rate decrease in bacteria (37). Similar circumstances may have occurred over the evolution of ST36, where multiple genomic deletions may lead to decreases in the growth rate of modern lineages of this clone, reducing the mutation rate because of a lower number of cell divisions.…”
Section: Discussionmentioning
confidence: 82%
“…This experimental evidence has pointed out one very important aspect of genome structure and function. Genome size increase is the result of horizontal gene transfer or DNA fragment retention that somehow is giving some beneicial features to recipient host, apparently an increase in itness [26]. The function of genes without evident function is still a relevant area of research since many of them provide support for itness and evolution has preserved them, therefore full genome engineering is far more complicated than previously thought.…”
Section: Genome Modiications To Understand E Colimentioning
confidence: 99%
“…The most relevant study revealed that genome size has an impact on E. coli cell growth, where it is shown that apparently dispensable sequences are needed under restrictive conditions, providing a hint of the still far future of fully functioning cells with all the desired characteristics for biotechnological applications [26]. We envision that genome reduction is a worthy efort, regardless of the method used to generate them.…”
Section: Genome Modiications To Understand E Colimentioning
confidence: 99%